2013
DOI: 10.1152/ajpendo.00546.2012
|View full text |Cite
|
Sign up to set email alerts
|

A form of mitofusin 2 (Mfn2) lacking the transmembrane domains and the COOH-terminal end stimulates metabolism in muscle and liver cells

Abstract: A form of mitofusin 2 (Mfn2) lacking the transmembrane domains and the COOH-terminal end stimulates metabolism in muscle and liver cells. Am J Physiol Endocrinol Metab 305: E1208 -E1221, 2013. First published August 13, 2013; doi:10.1152/ajpendo.00546.2012.-Mitofusin 2 (Mfn2), a protein that participates in mitochondrial fusion, is required to maintain normal mitochondrial metabolism in skeletal muscle and liver. Given that muscle Mfn2 is repressed in obese or type 2 diabetic subjects, this protein may have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…In contrast to aforementioned data it has been shown here that MEF cells with deleted Mfn2 gene exhibit substantially faster oxygen consumption than control fibroblasts. The interesting effects were observed by Segales et al (2013) [ 28 ], who found increased routine (basal) but not maximal oxygen consumption in myotubes and hepatoma FAO cells with silenced Mfn2 gene. However, this effect was attributed to increased oligomycin-insensitive proton leak.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to aforementioned data it has been shown here that MEF cells with deleted Mfn2 gene exhibit substantially faster oxygen consumption than control fibroblasts. The interesting effects were observed by Segales et al (2013) [ 28 ], who found increased routine (basal) but not maximal oxygen consumption in myotubes and hepatoma FAO cells with silenced Mfn2 gene. However, this effect was attributed to increased oligomycin-insensitive proton leak.…”
Section: Discussionmentioning
confidence: 81%
“…Similar stability of the ATP content was found in muscle cells depleted of Mfn2 gene. However, in those study oxidative metabolism was substantially reduced [ 26 , 28 ]. Moreover, recently Son et al (2015) have shown that in MEF cells Mfn1/2 depletion facilitates the glycolytic metabolic transition through the activation of the Ras-Raf and hypoxia-inducible factor 1α (HIF1α) signaling at an early stage of reprogramming [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that transgenic expression of a short form of Mfn2, which has no effect on mitochondrial morphology, stimulates glucose oxidation in skeletal muscle, and gluconeogenesis in liver, and enhances mitochondrial respiration in muscle and liver cells (Segales et al . ). Our results show that both type I and type II muscle fibres have profusion mitochondrial networks, with the diameter of the tubes and the fractional volume being larger in type I muscle fibres (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…() reported that Mfn2 deficiency leads to fragmented mitochondria and impairs insulin signalling in liver and muscle; however, as discussed above, the same group (Segales et al . ) has recently shown that Mfn2 has an effect on glucose metabolism regardless of mitochondrial morphology. Therefore, future studies investigating mitochondrial network structural organization and dynamics in high resolution are needed to investigate the effect of mitochondrial dynamics on cell metabolism and the spatial organization of the key players on/in the mitochondrial network.…”
Section: Discussionmentioning
confidence: 97%
“…Although Mfn2 is mostly known for its role in mitochondrial fusion, it also activates mitochondrial metabolism and increases the RC expression (Pich et al 2005). Specifically, mfn2 loss in skeletal muscle was characterized by reduced RC expression level and activity and impaired respiratory function (Segalés et al 2013). A loss of Kdm5a in Rb1 −/− MEFs resulted in a significant shift from glycolytic to oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%